Oxidative Dehydrogenation of n-Butane over LaV Catalysts Supported on TiO2 - Le Minh Cam; Ngo Duc Huyen; Nguyen Ngoc Ha (Journal of Chemistry)
The catalytic performance of vanadia catalysts with 15 wt% V supported on TiO2 and (15 wt% V + 4.6 wt% La) supported on TiO2 in oxidative dehydrogenation (ODH) of n-butane was investigated. The catalysts were characterized by means of TPD-NH3, TPR-H2, UV-Vis, and BET. Testing of samples showed that vanadia catalysts were active for the reaction. It was found that La doping of V/TiO2 catalyst had a negative effect on the dispersion of V species and led to formation of V2O5 clusters. This resulted in a loss of activity. Although slight improvement of selectivity was observed in comparison to undoped V/TiO2 samples due to lower acidity of La-doped –V/TiO2, this could not compensate the loss of activity and finally did not lead to higher butene yields.